BDNF repairs podocyte damage by microRNA‐mediated increase of actin polymerization. Issue 5 (7th January 2015) - Li, Min; Armelloni, Silvia; Zennaro, Cristina; Wei, Changli; Corbelli, Alessandro; Ikehata, Masami; Berra, Silvia; Giardino, Laura; Mattinzoli, Deborah; Watanabe, Shojiro; Agostoni, Carlo; Edefonti, Alberto; et al.
Abstract: Idiopathic focal segmental glomerulosclerosis (FSGS) is a progressive and proteinuric kidney disease that starts with podocyte injury. Podocytes cover the external side of the glomerular capillary by a complex web of primary and secondary ramifications. Similar to dendritic spines of neuronal cells, podocyte processes rely on a dynamic actin‐based cytoskeletal architecture to maintain shape and function. Brain‐derived neurotrophic factor (BDNF) is a pleiotropic neurotrophin that binds to the tropomyosin‐related kinase B receptor (TrkB) and has crucial roles in neuron maturation, survival, and activity. In neuronal cultures, exogenously added BDNF increases the number and size of dendritic spines. In animal models, BDNF administration is beneficial in both central and peripheral nervous system disorders. Here we show that BDNF has a TrkB‐dependent trophic activity on podocyte cell processes; by affecting microRNA‐134 and microRNA‐132 signalling, BDNF up‐regulates Limk1 translation and phosphorylation, and increases cofilin phosphorylation, which results in actin polymerization. Importantly, BDNF effectively repairs podocyte damage in vitro, and contrasts proteinuria and glomerular lesions in in vivo models of FSGS, opening a potential new perspective to the treatment of podocyte disorders. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.